HUBUNGAN PENERAPAN PERILAKU CERDIK DENGAN DERAJAT HIPERTENSI PADA PASIEN HIPERTENSI DI MASA PANDEMI COVID-19 - Tasya Darmatatya; Wan Nishfa; Reni Zulfitri (Jurnal Ners Indonesia, 2023)
CERDIK behaviour has an essential role in lowering blood pressure values. CERDIK consists of routine health checks, cigarette smoking cessation, diligent physical activity, a balanced diet, adequate rest, and managing stress. This study aims to determine the relationship between CERDIK behaviour and the degree of hypertension in hypertensive patients during the COVID-19 pandemic. This study uses a descriptive correlation design and a cross-sectional approach. The research sample was 98 respondents, selected based on inclusion criteria using a purposive sampling technique. CERDIK behaviour was assessed using a questionnaire developed by the researcher, and the degree of hypertension was measured using a digital sphygmomanometer. The statistical test used is Spearman Rho Test. Demographic data shows that most respondents are in the late elderly age at 41.8%, gender in the female category at 72.4%, last education is high school at 68.4%, housewife work at 62.2%, and hypertension <5 years at 78.6%. Statistical test results found a relationship with a p-value of 0.000 <0.05. CERDIK behaviour has a significant role in controlling hypertension. Health workers need to use a CERDIK behaviour approach to people with hypertension to prevent further problems.    Keywords: CERDIK behavior, degree of hypertension, COVID-19 Pandemic.